The new era of diabetes management: Comprehensive benefits of Ozempic in diabetes and co-morbidities - Aktar, Yasmin (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
The global health landscape is increasingly burdened by the rising prevalence of chronic conditions such as Type 2 Diabetes (T2D), obesity, cardiovascular disease (CVD), and chronic kidney disease (CKD), which are often interlinked through underlying metabolic dysfunction. This presentation provides an in-depth exploration of the multifaceted benefits of Ozempic (Semaglutide), a glucagon-like peptide-1 receptor agonist (GLP-1RA), as a cornerstone treatment for managing T2D and its associated comorbidities. Comorbidities like metabolic dysfunction-associated steatohepatitis (MASH) and cardiovascular complications are prevalent, underscoring the necessity of integrated treatment approaches. Clinical trial data from pivotal studies, such as the SUSTAIN and FLOW trials, evidenced remarkable outcomes, including up to 80% of patients achieving their HbA1c target of <7% and significant reductions in body weight with Ozempic. Furthermore, improvements in functional capacity, quantified as a mean increase in maximum walking distance (MWD) and substantial reductions in major adverse cardiovascular events (MACE), demonstrate the medication's impact not just on metabolic markers but also on overall health-related quality of life. The FLOW trial, specifically, revealed that semaglutide significantly reduces the risk of kidney disease progression, making it the only GLP-1RA with established protective effects on renal health. In conclusion, this presentation advocates for the recognition of semaglutide as an essential therapeutic agent in the holistic management of T2D. By addressing key risk factors and comorbidities through its diverse pharmacological effects, Ozempic represents a novel approach that not only targets hyperglycemia but also contributes significantly to the reduction of associated cardiovascular and renal complications, ultimately enhancing patient outcomes and quality of life. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S31]